An Exploratory Study about Patterns of Parental Home Literacy Activities during the COVID-19 Confinement among Spanish Families. Issue 6 (18th August 2021) - López-Escribano, Carmen; Escudero, Ana; Pérez-López, Raquel
ABSTRACT: Research Findings : The COVID-19 pandemic is leading to an unprecedented crisis worldwide. With schools closed, the frequency with which Spanish parents engage in home literacy activities with their children between the ages of 2 and 8 and the sociodemographic variables that influence this collaboration are unknown. The present research aimed to understand interactions among parents and children in the context of literacy activities at home. A total of 337 Spanish parents completed the Home Literacy Activities Questionnaire (HLAQ). Results from the reliability test showed a good adequacy and consistency (Cronbach's alpha .85), and a factorial analysis indicated all items could be grouped into four factors: reading activities, writing activities, digital literacy activities, and dialogic-creative literacy activities. A latent class cluster analysis, based on parents' factorial scores in the HLAQ and their sociodemographic data, suggested four discrete parental clusters: parents prioritizing writing activities, interested in practicing all type of literacy activities, willing to do digital activities, or ready to practice dialogic-creative literacy activities. All indicators and sociodemographic characteristics – the children's age, the number of children in the family, and the parents' educational level – were significant and discriminated among the parental clusters. The activities carried out with least frequency were dialogic-creative literacy activities and digital literacy activities. Practice or Policy : Schools, as well as researchers, must be intentional about engaging families who may not be aware of certain activities to support their young children's literacy skills, in times of crisis, for all children and families, for specific groups of families and children, and at varying grade levels.